Vo2 Max Atlet Taekwondo - Rakha Aqil Furqan; sonya nelson; Septri; Donal Syafrianto (Jurnal IKEOR, 2024)
The Effect of Interval Training on Increasing Vo2Max for Taekwondo Athlete Dojang Kodim 03/04 Agam, Bukittinggi. ​The problem with this research is that interval training is rarely used in physical training for taekwondo athletes. Dojang Kodim 03/04 Agam, Bukittinggi. And researchers want to investigate the extent to which athletes' lack of understanding about interval training can affect their ability to increase Vo2Max, where physical condition greatly influences performance athlete. Therefore, researchers are interested in knowing the effect of interval training on increasing the Vo2Max of Taekwondo Athletes at Dojang Kodim 03/04 Agam, Bukittinggi. This research uses a quasi-experimental method, which means that the researcher cannot fully control the sample with a One Group Pretest Posttest Design. The population in this study was 162 athletes, consisting of 72 women and 90 men, and the sampling technique was purposive sampling, which is a sample determination technique with certain considerations, including an age range of 13-16 years and male gender, so The number of samples in this study was 15 people. The instrument is the MFT (Multi Fitness Test) Bleep Test. The analysis technique uses the t-test with a level of α = 0.05. Based on the research results, the tcount value was 8.449 > ttable 1.761, so there is a significant influence. So it can be concluded that there is an influence of interval training on increasing the Vo2Max of Taekwondo Athlete Dojang Kodim 03/04 Agam, Bukittinggi Pengaruh Latihan interval terhadap Peningkatan Vo2Max atlet Taekwondo Dojang Kodim 03/04 Agam, Bukittinggi. Permasalahan pada penelitian ini adalah latihan interval jarang sekali digunakan pada latihan fisik atlet taekwondo Dojang Kodim 03/04 Agam, Bukittinggi Serta peneliti ingin menyelidiki sejauh mana kurangnya pemahaman atlet tentang Latihan interval dapat mempengaruhi kemampuan mereka untuk meningkatkan Vo2Max, yang mana kondisi fisik sangat mempengaruhi peforma atlet. Maka dari itu peneliti tertarik untuk mengetatui pengaruh latihan interval terhadap Peningkatan Vo2Max Atlet Taekwondo Dojang Kodim 03/04 Agam, Bukittinggi. ​Penelitian ini menggunakan metode eksperimen semu yang berarti bahwa peneliti tidak dapat mengontrol penuh sampel dengan rancangan One Group Pretest Posttest Design. Populasi dalam penelitian ini adalah 162 Atlet , yang terdiri dari 72 orang perempuan dan 90 Laki-laki, dan teknik pengambilan sampelnya yaitu Purposive sampling adalah teknik penentuan sampel dengan pertimbangan tertentu antara lain rentang usia 13-16 tahun dan berjenis kelamin laki-laki, maka jumlah sampel pada penelitian ini adalah 15 Orang. Instrumen berupa tes MFT (Multi Fitness Test) Bleep Test. Teknik analisis menggunakan uji-t dengan taraf α = 0,05. ​Berdasarkan hasil penelitian maka diperoleh nilai thitung 8,449 > ttabel1,761 maka terdapat pengaruh yang signifikan. Maka dapat ditarik kesimpulan bahwa terdapat pengaruh latihan interval Terhadap peningkatan Vo2Max Atlet Taekwondo Dojang Kodim 03/04 Agam, Bukittinggi.